2011
DOI: 10.3899/jrheum.100665
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Certolizumab Pegol with Other Anticytokine Agents for Treatment of Rheumatoid Arthritis: A Multiple-treatment Bayesian Metaanalysis

Abstract: Objective.To compare the clinical efficacy of certolizumab pegol (CZP) with that of other anticytokine agents indicated for the treatment of rheumatoid arthritis (RA) with identical therapeutic indication (anti-tumor necrosis factor-α, anti-interleukin 1 or 6), with the objective of determining the noninferiority of CZP.Methods.A systematic review was performed to identify randomized controlled trials that assessed the efficacy of anticytokine agents in combination with conventional disease-modifying antirheum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
2

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 39 publications
1
24
0
2
Order By: Relevance
“…A number of indirect comparisons have been performed to date3 4 6 8 11 38 39; this is the first such that examines the HAQ improvement incorporating baseline disease severity in a Bayesian framework. The value of MTC to evidence-based healthcare evaluations was recently highlighted 40.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of indirect comparisons have been performed to date3 4 6 8 11 38 39; this is the first such that examines the HAQ improvement incorporating baseline disease severity in a Bayesian framework. The value of MTC to evidence-based healthcare evaluations was recently highlighted 40.…”
Section: Discussionmentioning
confidence: 99%
“…Five of these studies have used a Bayesian method to combine the evidence46 10 11; the remaining studies used a frequentist approach. The outcomes chosen for these analyses have primarily been American College of Rheumatology (ACR) response.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of The Journal, Launois, et al apply Bayesian methods of metaanalysis to evaluate the non-inferiority of certolizumab with other anticytokine agents for the treatment of rheumatoid arthritis 8 . Traditionally, metaanalysis is used to synthesize data from multiple studies.…”
Section: Examplementioning
confidence: 99%
“…However, it has been reported that substantial numbers of patients with autoimmune diseases still do not respond to one or more anticytokine biological agents. Among biological agents, TNF inhibitors have been extensively investigated with regard to the frequency of inadequate responders (Launois et al, 2011;Lovell et al, 2008;Maini et al, 2006;Yokota et al, 2008), because anti-TNF antibodies were the first agents approved as the therapy of RA. For example, 20~40 % of patients treated with a TNF inhibitor failed to achieve an improvement of 20 % in American College of Rheumatology criteria Rubbert-Roth and Finckh, 2009).…”
Section: Wwwintechopencommentioning
confidence: 99%